2022
DOI: 10.3390/jof8060636
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sodium Bicarbonate (SBC) with Bacterial Antagonists for the Control of Brown Rot Disease of Fruit

Abstract: Simultaneous treatment with antagonistic bacteria Bacillus amylolquefaciens (SF14), Alcaligenes faecalis (ACBC1), and the food additive sodium bicarbonate (SBC) to control post-harvest brown rot disease caused by Monilinia fructigena, and their effect on the post-harvest quality of nectarines were evaluated. Four concentrations of SBC (0.5, 2, 3.5, and 5%) were tested. Results showed that bacterial antagonists displayed remarkable compatibility with different concentrations of SBC and that their viability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(79 reference statements)
0
9
0
Order By: Relevance
“… Castro-Ríos et al (2021) reported that 3.0 g/L SBC presented a significant reduction in A. niger growth 72 h after inoculation. Some researchers speculated that pH may be involved in the inhibitory activity of SBC since SBC could change the pH of the growth environment of microbes ( Lyousfi et al, 2022 ). Lai et al (2015) found that pH could induce different expressions of some genes, resulting in the inhibition of the growth of P. expansum .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Castro-Ríos et al (2021) reported that 3.0 g/L SBC presented a significant reduction in A. niger growth 72 h after inoculation. Some researchers speculated that pH may be involved in the inhibitory activity of SBC since SBC could change the pH of the growth environment of microbes ( Lyousfi et al, 2022 ). Lai et al (2015) found that pH could induce different expressions of some genes, resulting in the inhibition of the growth of P. expansum .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that SBC plays an important role in the inhibition of postharvest diseases in several fruits. For example, SBC controls postharvest diseases caused by P. digitatum ( Zhu et al, 2012 ), Penicillium italicum , Geotrichum citri-aurantii ( Hong et al, 2014 ), and Monilinia fructigena ( Lyousfi et al, 2022 ). Nonetheless, similar to other alternative treatments, its application alone shows much lower effectiveness compared to synthetic fungicides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the combined use of sodium bicarbonate and a bacterial antagonist demonstrated signi cant inhibitory effects on both mycelial growth and spore germination of M. fructigina, resulting in a fungal inhibition rate ranging from 60.97% to 100%. Conversely, when sodium bicarbonate or a bacterial antagonist was used individually, the inhibition rates were lower, ranging from 9.27% to 64.83% [9] .…”
Section: Antifungal Mechanism Of Combinationmentioning
confidence: 94%
“…A combination of microbial biocontrol agents and other chemical components has been reported to increase biocontrol efficacy. For instance, many salt additives, such as calcium chloride, sodium carbonate, and sodium bicarbonate, along with microbial biocontrol agents efficiently controlled diseases in fruits and vegetables [ 18 , 19 ]. Silicon, the second most abundant element (27%) in the earth’s crust, is usually present in unavailable forms of silicates that cannot be readily used by plants [ 20 ].…”
Section: Introductionmentioning
confidence: 99%